Does the Steindl-Dutt investment function rule out profit-led expansion? - Deepankar Basu (University of Massachusetts, Department of Economics, 2018)
Bhaduri and Marglin (1990) had argued that an investment function which has the profit rate and the capacity utilization rates as the two determinants of investment imposes unwarranted restrictions on the macroeconomic model and rules out profit-led expansion. In this paper, I show that this critique only holds in a closed economy model. In an open economy model, such an investment function does not rule out profit-led expansion. I argue that the problem was less in the investment function itself than in the larger model within which it was embedded, in particular the saving behavior of the macroeconomy entailed by the model.
Keywords: E12; B51; 330; structuralist model; investment function; profit-led expansion